Incidents resulting in health care among older people with intellectual disability in comparison with the general population: A national register study. Issue 2 (2nd April 2020) - Axmon, Anna; Ekwall, Anna; Ahlström, Gerd
ABSTRACT: Background: Older people with intellectual disability (ID) are at high risk of incidents leading to hospital visits. Method: Through national registers, 7936 people with ID, aged 55+ years in 2012, and a same-aged referent cohort from the general population were identified. Information on diagnoses made in inpatient and outpatient specialist health care during 2002–2012 was collected. Results: Compared to their age-peers in the general population, people with ID were 41% more likely to seek care for effects of foreign body entering through natural orifice, and 92% more for poisoning by drugs, medicaments and biological substances. Conclusions: There is a need to develop and evaluate evidence-based interventions to prevent unnecessary suffering and early death related to poisoning or respiratory diseases among older people with ID. To do this, implementation of risk assessments and increased knowledge of the consequences of poisoning and incidents of foreign bodies entering the respiratory organs are necessary.